Detection of weapon possession and fire in Public Safety surveillance cameras - Moura, Natan Santos; Gondim, João Medrado; Claro, Daniela Barreiro; Souza, Marlo; Figueiredo, Roberto de Cerqueira (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2021: Anais do XVIII Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2021.18261, 2021)
The employment of video surveillance cameras by public safety agencies enables incident detection in monitored cities by using object detection for scene description, enhancing the protection to the general public. Object detection has its drawbacks, such as false positives. Our work aims to enhance object detection and image classification by employing IoU (Intersection over Union) to minimize the false positives and identify weapon holders or fire in a frame, adding more information to the scene.